Utilizing Hydrophobic Sand to Construct an Air-Permeable Aquiclude to Enhance Rice Yield and Lodging Resistance - Xiaoyan Ma; Jing Wu; Yuming Su; Shengyi Qin; Francesco Pilla (Agronomy)
Global climate change and persistent droughts lead to soil desertification, posing significant challenges to food security. Desertified lands, characterized by high permeability, struggle to retain water, thereby hindering ecological restoration. Sand, a natural resource abundant in deserts, inspired our proposal to design hydrophobic sand and construct Air-permeable Aquicludes (APAC) using this material. This approach aims to address issues related to the ecological restoration of desertified lands, food security, and the utilization of sand resources. Reclamation of desertified land and sandy areas can simultaneously address ecological restoration and ensure food security, with soil reconstruction being a critical step. This study investigated the effects of constructing an Air-permeable Aquiclude (APAC) using hydrophobic sand on rice yield and lodging resistance, using clay aquitard (CAT) and plastic aquiclude (PAC) as control groups. The APAC enhanced soil oxygen content, increased internode strength, and improved vascular bundle density, substantially reducing the lodging index and increasing yield. This research finds that the APAC (a) increased internode outer diameter, wall thickness, fresh weight, and filling degree; (b) enhanced the vascular bundle area by 11.11% to 27.66% and increased density; (c) reduced the lodging index by 37.54% to 36.93% (p < 0.01); and (d) increased yield to 8.09 t·hm−2, a rise of 12.05% to 14.59% (p < 0.05), showing a negative correlation with lodging index. These findings suggest that APAC has very good potential for desertified land reclamation and food security. In conclusion, the incorporation of hydrophobic sand in APAC construction considerably strengthens rice stem lodging resistance and increases yield, demonstrating considerable application potential for the reclamation of desertified and sandy land and ensuring food security.